The Damsel in Distress in Kants Critique of pure Reason - on the ambivalence of reason between disciplin and self-liberation - Wallner, Larissa (Con-Textos Kantianos. International Journal of Philosophy, 2024)
This article explores an overlooked motif in the Critique of Pure Reason: the “Damsel in Distress.” Kant uses the trope to motivate his first Critique on a narrative level. Reason is depicted as a high-born female subject in a hopeless predicament, unable to free herself. A hero rescues her, not by liberation, but by discipline, mirroring the myth where the rescued female is appropriated through marriage. The paper examines the parallels between this popular trope and the narrative of the first Critique, arguing that Kant’s choice of this motif is due to cultural and political biases. While this narrative aligns with Kant’s goal of establishing philosophy as a strict science, it marginalizes the also present, progressive potential of Kant’ s concept of the highest faculty as a hermeneutical, world-making, and orienting capacity as means for universal cum critical thinking.
Keywords: metaphor-analysis; reason; women; methodology; feminist Kantianism